FSH Beyond Fertility - Lizneva, Daria; Rahimova, Alina; Kim, Se-Min; Atabiekov, Ihor; Javaid, Seher; Alamoush, Bateel; Taneja, Charit; Khan, Ayesha; Sun, Li; Azziz, Ricardo; Yuen, Tony; Zaidi, Mone (Frontiers in Endocrinology, 2019)
The traditional view of follicle-stimulating hormone (FSH) as a reproductive hormone is changing. It has been shown that FSH receptors (FSHRs) are expressed in various extra-gonadal tissues and mediats the biological effects of FSH at those sites. Molecular, animal, epidemiologic, and clinical data suggest that elevated serum FSH may play a significant role in the evolution of bone loss and obesity, as well as contributing to cardiovascular and cancer risk. This review summarizes recent data on FSH action beyond reproduction.